2021
DOI: 10.1186/s12859-021-04113-8
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering hierarchical organization of topologically associated domains through change-point testing

Abstract: Background The nucleus of eukaryotic cells spatially packages chromosomes into a hierarchical and distinct segregation that plays critical roles in maintaining transcription regulation. High-throughput methods of chromosome conformation capture, such as Hi-C, have revealed topologically associating domains (TADs) that are defined by biased chromatin interactions within them. Results We introduce a novel method, HiCKey, to decipher hierarchical TAD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 79 publications
0
12
0
Order By: Relevance
“…The degree of TAD boundary conservation was evaluated using a permutation test, where the number of boundaries being shared across cell types was compared against a background derived from merging the list of boundaries and shuffling cell type labels. Additionally, 9 other TAD identification algorithms (Levy‐Leduc et al , 2014; Rao et al , 2014; Shin et al , 2016; preprint: Dali et al , 2018; An et al , 2019; Cresswell et al , 2020; Matthey‐Doret et al , 2020; Soler‐Vila et al , 2020; Xing et al , 2021) were used with default parameters to validate trends observed with insulation scores, all at 50 kb resolution.…”
Section: Methodsmentioning
confidence: 99%
“…The degree of TAD boundary conservation was evaluated using a permutation test, where the number of boundaries being shared across cell types was compared against a background derived from merging the list of boundaries and shuffling cell type labels. Additionally, 9 other TAD identification algorithms (Levy‐Leduc et al , 2014; Rao et al , 2014; Shin et al , 2016; preprint: Dali et al , 2018; An et al , 2019; Cresswell et al , 2020; Matthey‐Doret et al , 2020; Soler‐Vila et al , 2020; Xing et al , 2021) were used with default parameters to validate trends observed with insulation scores, all at 50 kb resolution.…”
Section: Methodsmentioning
confidence: 99%
“…Xing et al [ 84 ] developed a statistical model of TADs called HiCKey, which identifies TADs in two main steps: (1) initially, the method proposes a generalized likelihood-ratio test to detect transition points in given interaction matrix which can follow general mixture or negative binomial distribution, (2) the method runs a number of search strategies to infer hiearchical TADs with their associated p values calculated by the generalized likelihood-ratio test. HiCKey can use an Hi-C matrix as input data and has three key parameters: lower bound of TAD size, threshold to test whether a boundary (change-point) is significant, threshold for identifying nested TADs.…”
Section: Methodsmentioning
confidence: 99%
“…HiCKey 21 was used to detect topologically associated domains (TADs) and HiCCUPS to detect chromosome loops 22 , revealing distinct chromosomal organizations associated with biosynthetic gene clusters. For example, STR and TDC are physically clustered on chromosome 3 (Fig.…”
Section: Biosynthetic Gene Clusters and Associated Chromosome Conform...mentioning
confidence: 99%